2021
DOI: 10.1089/tmj.2020.0186
|View full text |Cite
|
Sign up to set email alerts
|

Telecritical Care Clinical and Operational Strategies in Response to COVID-19

Abstract: Background: The cororavirus disease 19 (COVID-19) pandemic has strained intensive care unit (ICU) material and human resources to global crisis levels. The risks of staffing challenges and clinician exposure are of significant concern. One resource, telecritical care (TCC), has the potential to optimize efficiency, maximize safety, and improve quality of care provided amid large-scale disruptions, but its role in pandemic situations is only loosely defined. Planning and Preparation Phase: We propose strategic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 30 publications
0
16
0
1
Order By: Relevance
“…As a response to this international public health crisis, scientists and clinicians have made enormous efforts in the last few months to generate new knowledge and to develop technological tools that may help in combating this infectious disease and mitigate its effects. Some of these efforts include the development of drugs and vaccines [ 1 4 ], the construction of epidemiological models to forecast the dynamics of disease spreading in the population [ 5 – 8 ], the development of mobile-device applications for tracking infected patients and new cases [ 9 11 ], and the development of strategies and the application of new technologies to manage the resources and capacities in hospitals [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a response to this international public health crisis, scientists and clinicians have made enormous efforts in the last few months to generate new knowledge and to develop technological tools that may help in combating this infectious disease and mitigate its effects. Some of these efforts include the development of drugs and vaccines [ 1 4 ], the construction of epidemiological models to forecast the dynamics of disease spreading in the population [ 5 – 8 ], the development of mobile-device applications for tracking infected patients and new cases [ 9 11 ], and the development of strategies and the application of new technologies to manage the resources and capacities in hospitals [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the Atrium Health study performed by Singh et al, virtual critical care augmentation was found to be more cost-effective than structural changes, though the initial investment in home workstations required extensive set-ups and support from their Information Technology department [ 22 ]. The Singh study found that teleintensivists worked well with triaging interfacility transfer decisions and resource utilization and noted that this was well received by physicians who had an intimate knowledge of hospital resources [ 22 ]. The role changes inherent in a hybrid virtual and in-person team initially created confusion, which was eventually overcome with frequent and intense communication strategies [ 22 ].…”
Section: Reviewmentioning
confidence: 99%
“…The Singh study found that teleintensivists worked well with triaging interfacility transfer decisions and resource utilization and noted that this was well received by physicians who had an intimate knowledge of hospital resources [ 22 ]. The role changes inherent in a hybrid virtual and in-person team initially created confusion, which was eventually overcome with frequent and intense communication strategies [ 22 ].…”
Section: Reviewmentioning
confidence: 99%
“…As a response to this international public health crisis, scientists and clinicians have made enormous efforts in the last few months to generate new knowledge and to develop technological tools that may help in combatting this infectious disease and mitigate its effects. Some of these efforts include the development of drugs and vaccines [1][2][3][4], the construction of epidemiological models to forecast the dynamics of disease spreading in the population [5][6][7][8], the development of mobile-device applications for tracking infected patients and new cases [9][10][11], and the development of strategies and the application of new technologies to manage the resources and capacities in hospitals [12][13][14].…”
Section: Introductionmentioning
confidence: 99%